Pemikiran Taqiyuddin An-Nabhani dan Yusuf Al-Qaradhawi Tentang Sewa Menyewa Lahan Pertanian Relevansi Masyarakat Petani di Indonesia - Mona Ely Sukma; Nofiardi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
After in-depth study, it can be concluded that Taqiyuddin an-Nabhani put forward several regulations regarding the rental of agricultural land. It requires every agricultural land owner to manage the land optimally and prohibits renting out agricultural land for rent in the form of food or produce from the land. Apart from that, he also prohibits renting out land for a third or a quarter of the proceeds. On the other hand, Yusuf al-Qaradawi also has a similar view. According to him, every land owner should manage his own land. He prohibits renting out land for money, dirhams or dinars, both in the long and short term. In terms of differences between the two opinions, the aspect of renting agricultural land lies in the muzara'ah contract. Taqiyuddin an-Nabhani is legally prohibited from renting agricultural land with a muzara'ah agreement. Meanwhile, Yusuf al-Qaradawi rented agricultural land with a muzara'ah agreement, which was permitted with the encouragement of ta'awun. These two figures have their own special features in exploring these thoughts. The hadith used by each figure has strengths and weaknesses. Taqiyuddin an-Nabhani is based on the istinban method carried out by Taqiyuddin an-Nabhani using the arguments of the Al-Qur'an, As-Sunnah, ijma friends and Qiyas as one of his ijtihad methods. On the other hand, Yusuf al-Qaradawi also used hadith, but he also used qiyas as his method. It can be concluded that these two scholars expressed their opinions in the context of leasing agricultural land which is relevant for farming communities in Indonesia. It is hoped that the implementation of this law can create justice in the rental system, avoid chaos, and pay attention to the benefit of the Indonesian people from a political perspective. However, from the perspective of other scholars, they actually allow rental transactions for agricultural land based on the quality of the strength of this argument.